Normative Gaps in Indonesia’s Capital Relocation: Constitutional Implications of State Function Transition to Nusantara - Edi Saputra; Eman Suparman; Zainal Muttaqin; Serhii Ablamskyi (Sekolah Tinggi Hukum Bandung, 2024)
The relocation of Indonesia’s capital is a strategic constitutional decision with significant legal consequences. While Law Number 3 of 2022 formally designates Nusantara as the new capital, it fails to regulate the transition of core state functions. This research aims to identify the normative gaps in the law, focusing on the absence of two key indicators: a legally defined effective date of relocation and the formal transfer of executive, legislative, and judicial functions. This research specification is descriptive in nature and employs a normative legal method as type of research. The conceptual approach is applied to explore legal doctrines to provide a broader legal perspective, the research also employs a comparative approach. Data is collected through a literature review, and analyzed qualitatively through interpretive reasoning and legal argumentation to formulate normative conclusions relevant to the issues discussed. The lack of transitional provisions undermines legal certainty and the legitimacy of government actions taken in Nusantara. The article argues for an urgent reformulation of transitional instruments to restore coherence between political declarations and constitutional order.